2023
DOI: 10.4103/jpbs.jpbs_661_22
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dentofacial Harmony among Young and Old Adult Females in Smile Perception of Dental Specialists and Laypeople: A Cross-Sectional Study

Abstract: Introduction: The purpose of this study was to determine whether balance and harmony of the face, when seen as a whole, alter the smile perception as compared to a lone standing smile in female subjects of two age groups and to identify parameters of dental composition and dentofacial harmony associated with the smile perception of dental specialists (DS) and laypeople (LP). Settings and Design: A cross-sectional study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…A previous study has shown that a reference point for determining the appropriate dimension of the buccal corridor might be the distance from the proximal of the pupil and the terminal region of the iris [14]. It has been previously shown that, when employing a lower facial viewpoint, laypeople can accurately distinguish the standard and various degrees of acceptableness [15], which is in accordance with our results, demonstrating how different backgrounds can have fluctuating look-up patterns for a variety of factors. In terms of skin assessment, all the participants considered it extremely important.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study has shown that a reference point for determining the appropriate dimension of the buccal corridor might be the distance from the proximal of the pupil and the terminal region of the iris [14]. It has been previously shown that, when employing a lower facial viewpoint, laypeople can accurately distinguish the standard and various degrees of acceptableness [15], which is in accordance with our results, demonstrating how different backgrounds can have fluctuating look-up patterns for a variety of factors. In terms of skin assessment, all the participants considered it extremely important.…”
Section: Discussionsupporting
confidence: 91%